Calcium and CA 15-3 Level in Breast Cancer Patients Pre- and Post-Mastectomy Surgery - Kirom, Umi Aminotul; Santosa, Budi; Limijadi, Edward Kurnia Setiawan (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2025)
Breast cancer has a potentially affect the calcium levels because of its role in regulating cell proliferation, differentiation, migration, invasion, metabolism, and apoptosis. Analysis related to changes in calcium levels in breast cancer patients can contribute to developing patient treatment plans. CA 15-3 is a protein made primarily by breast cancer cells and is an epitope of the transmembrane glycoprotein (MUC1). High concentrations of calcium and CA 15-3 levels are associated with tumor burden and prognostic factors for breast cancer. This study aims to prove that there are differences in the results of an examination of calcium levels and CA 15-3 in breast cancer patients before and after mastectomy surgery. In this study, 50 female patients who were diagnosed with stage I, II, and III breast cancer had their serum CA 15-3 levels and calcium levels checked before and 10 days after surgery. The research analysis used for this difference test is the paired T-test and the Wilcoxon test. In this study, it was found that CA 15-3 levels decreased after breast surgery. Mean calcium levels before surgery were (10.092+1.2762 mg/dL). Mean calcium levels after surgery were (8.489+1.0204 mg/dL). CA 15-3 levels before surgery were 26.895+18.4914 UI/mL and after surgery were 21.678+11.9711 UI/mL. It can be concluded that there was a decrease in calcium levels of 1.603 mg/dL, and CA 15-3 levels decreased by 5.217 UI/mL between before and after mastectomy surgery.